Report of the task force on tax administration - Task Force on Tax Administration, Federal Republic of Nigeria; Task Force on Tax Administration (Lagos : Task Force on Tax Administration, 1979)
This is a report of the task force on tax administration established by the military administration of the Federal Republic of Nigeria in April 1978. The report: examines sources of revenue and the structure of tax administration in Nigeria; assesses the effectiveness in the management of existing taxes at the federal and state levels; and suggests ways and means toe make the administration of tax in Nigeria more efficient.
lje 5/3/19
Arch
Keywords: Taxation; Taxation -- Law and legislation; Nigeria